Model Pembelajaran Kelas Percakapan pada Masa Pandemi - Sri Rahayuni, Ni Ketut (International Seminar on Austronesian Languages and Literature, 2021)
English is currently a language skill that everyone in the world wants to master because English is one of the international languages ??used by many countries. In some countries, English is the second language for the people, because the role of English as an international communication language is very important for various existing sectors, and Indonesia is one of the countries that now uses English as a second language, although not or not all Indonesian people do it. This has been seen by Udayana University as an attractive university in Indonesia. One of the faculties, namely the Faculty of Economics and Business, has included Conversation Practice courses in its curriculum for Diploma 3 students. This course is obtained by 3rd semester students. During the current Covid-19 pandemic, the right learning model must be a good consideration for students. teacher to suit the current situation. This research is important to do in order to find out how the learning model has been running during the pandemic for English Conversation (conversation) practice classes for D3 students of the Faculty of Economics and Business by implementing online lectures without direct lectures in class. The data sources in this study were a number of D3 program students in the Faculty of Economics and Business, Udayana University who received English lectures. The method of collecting data is by documentation. In analyzing the data, a qualitative descriptive method will be used to obtain a more in-depth explanation of the analysis of the needs of learning English in D3 program students in the Faculty of Economics and Business, Udayana University. The theory that will be used in analyzing the data is the theory of needs analysis by Morrison (2001).